(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
This essay focuses on characterizing the production systems present in San Nicolas, Estelí. To meet the overall objective has been raised the following specific objective is to develop a typology of peasant farms and production systems present in the Garnacha. The argument is that in the surveyed community producers continue agricultural production pattern with little tendency towards diversification and a greater tendency towards the production of basic grains. The methodology is exploratory in nature because it seeks information on qualitative and quantitative data to identify patterns of farming systems. The information was collected through surveys of producers in the municipality of San Nicolas, Estelí. It was found that the producers have problems in their crop yields, the type of property and land use potential verifies more diversified producers but for larger trend according to the typology created. REICE Vol.3(6) 2015: 194-215